Agri-Iot: a Sustainable Environment for Improvement of Crops Revenue in the Field of Agriculture Using Iot - S.Hrushikesava Raju, Dr; M.Nagabhushana Rao, Dr; N.Sudheer, Dr; P.Kavitharani, Dr (International Journal of Engineering and Technology, 2018)
Agriculture is a field where farmers experience less income because of natural disorders like less rain fall, floods, lack of weather forecasting at the farmers end, unaware of technology to use for their crop benefit, lack of automatic functioning of equipment, lack of interconnection among the components involved in the process and most of other bad experiences. To lift the farmers life not only in the stateâ€™s economy and also in any nationâ€™s economy, a technology to be needed that will help the crops to get yieldingâ€™s in time without any delays, and also make merchants to contact the farmers directly by offering the high prices for the quality crop yieldingâ€™s. The proposed technique called Internet of Things (IoT) is a new technology which is adapted for the agriculture field for increasing the farmers crop revenue. This developed IoT design in which components required such as sensors, motors, transmitters, and other required devices to function in the integrated collaboration of internet. The expected results are noted in the Results chapter and are found necessary for future generations of farmers. This design and functioning of the IoT for the agriculture is proven the best approach to follow in this modern world.Â Â Â